2020
DOI: 10.1177/0022034520920577
|View full text |Cite
|
Sign up to set email alerts
|

Niche Specific Microbiota-Dependent and Independent Bone Loss around Dental Implants and Teeth

Abstract: Oral mucosal homeostasis is achieved by complex immunologic mechanisms, orchestrating host immunity to adapt to the physiologic functions of the various specialized niches in the oral cavity. Dental implants introduce a novel mucosal niche to the immune system to deal with. Nevertheless, the immune mechanisms engaged toward implants and whether they have broader effects are not well defined. Using a murine model, we found an accumulation of neutrophils and RANKL-expressing T and B lymphocytes in the implant-su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…Since the last decade, despite the dental implants in function for the first year, more than 2 mm bone loss around the dental implant indicates peri‐implantitis in general 30‐32 whereas not liner pattern of the bone loss has been reported previously 33 . Normally, the occurrence of peri‐implantitis develops after passing the initial years of the in‐function dental implant.…”
Section: Discussionmentioning
confidence: 99%
“…Since the last decade, despite the dental implants in function for the first year, more than 2 mm bone loss around the dental implant indicates peri‐implantitis in general 30‐32 whereas not liner pattern of the bone loss has been reported previously 33 . Normally, the occurrence of peri‐implantitis develops after passing the initial years of the in‐function dental implant.…”
Section: Discussionmentioning
confidence: 99%
“…The mucosal tissues and lymph nodes (LNs) were processed as previously reported (Heyman et al, 2018(Heyman et al, , 2020. In short, a circumference of 1 mm of gingiva around teeth or PIM surrounding implants, containing infiltrated connective tissue (ICT) and healthy tissue, were harvested.…”
Section: Isolation and Processing Of The Gingiva And Peri-implant Muc...mentioning
confidence: 99%
“…Using this model, we demonstrated that implants dysregulate immune response in the peri-implant mucosa (PIM). The inflammatory milieu contained higher levels of neutrophils, monocytes, lymphocytes, and RANKLexpressing CD4 + T and B cells, together with high expression levels of pro-inflammatory cytokines and a high IL17A/Foxp3 ratio compared to control tissue surrounding the teeth (Heyman et al, 2018(Heyman et al, , 2020. This altered, inflamed condition in the PIM, referred to as "dysregulated homeostasis", may explain the increased susceptibility of implants in humans to infection and the consequent rapid deterioration of the supporting tissues (Carcuac & Berglundh, 2014;Salvi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Osteolytic mediators such as receptor of NF-κB, RANKL, and Wnt5a, as well as proteinases such as matrix metalloproteinase-2, matrix metalloproteinase-9, and cathepsin-K are also reportedly upregulated in peri-implantitis sites compared to controls ( Kensara et al., 2021 ). It is worth noting that implants have an impact on remote periodontal sites, as elevated inflammation and accelerated bone loss have been detected in intact, distant teeth ( Heyman et al., 2020 ). That impact was due to microbial dysbiosis induced by the implants, since antibiotic treatment was demonstrated to prevent periapical bone loss.…”
Section: Oral Microbiota In Alveolar Bone Formation and Bone Lossmentioning
confidence: 99%
“…That impact was due to microbial dysbiosis induced by the implants, since antibiotic treatment was demonstrated to prevent periapical bone loss. However, antibiotic treatment does not prevent the loss of implant-supporting bone, highlighting the distinct mechanisms mediating bone loss at each site ( Heyman et al., 2020 ).…”
Section: Oral Microbiota In Alveolar Bone Formation and Bone Lossmentioning
confidence: 99%